Editorial Comment: The Academy and Ecumenism - Vance, Stanley Editor (Academy of Management Journal, 1967)
The author comments on how ecumenical trends in business affect the area of management theory. The author discusses the ecumenical trends he witnessed at the International Meetings of The Institute of Management Sciences (TIMS) on August 20-25, 1967, such as noticing the international character of the meetings and the wide subject areas of study of the attending colleges. The author discusses the admission standards of the Academy of Management, and warns that if the Academy moves in the ecumenical direction and includes more members in its scope, the organization must be prepared for the influx of people and subject matters at its meetings.